Diaper dermatitis and associated factors among children aged 0–24 months in low- and middle-income countries: A systematic review protocol - Atoma Negera; Midekso Sento; Debela Dereje; Gamachis Firdisa; Samuel Negera; Geleta Nenko; Tadesse Sime; Merga Keba (PLoS ONE, 2025)
Background Diaper dermatitis (DD, sometimes known as diaper rash or napkin dermatitis is one of the most prevalent skin infections that occur in the area covered by the diaper. Although diaper dermatitis can be seen in any patient wearing diapers, it is reported to be more common in infants aged 9–12 months. Approximately, 70% of infants and young children suffer from diaper dermatitis at some point during their diaper wearing years and up to 25% of children seek healthcare due to this case. Methods and analysis: Methods and analysis A comprehensive literature search will be gathered from electronic databases such as PubMed, Embase, Hinari, Cochrane Library, African Journals Online (AJOL), and Google Scholar. The protocol followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses for Protocol (PRISMA-P) guideline. All studies conducted in low- and middle-income countries (LMICs) will be included regardless of their study design as long as these studies report the magnitude of the problem under study. Joanna Briggs Institute’s (JBI) appraisal checklist will be used to assess the quality of individual studies. Heterogeneity will be checked using Cochrane Q test statistics and I2 test statistics, and a random-effects model will be employed to estimate the pooled prevalence of DD and its associated factors. Ethics and dissemination of research Ethics committee approval or written informed consent will not be required to conduct this review, and meta-analysis for the review will be entirely based on published data. The result of this study will be submitted to a peer-reviewed journal, and it will also be presented at relevant research conferences. Results The present study will estimate the pooled prevalence of diaper dermatitis and their associated factors in low- and middle-income countries. Trial registration PROSPERO registration number: CRD42024578550.